1998
DOI: 10.1183/09031936.98.12020395
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke inhalation and lung damage in smoking volunteers

Abstract: Cigarette smoking is the dominant risk factor for the development of chronic obstructive pulmonary disease (COPD) [1,2], but only 10-15% of smokers develop the condition [1]. Several risk factors for COPD are known [2] but only apply to a small minority of cases. There is only a weak relationship between the lifetime number of cigarettes smoked and risk of COPD [2,3]. Smoke must be inhaled to damage the lung and it is the cumulative dose of smoke inhaled that would seem to be relevant to the development of lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0
9

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 22 publications
4
13
0
9
Order By: Relevance
“…Other authors have found that a distinct tobacco inhalation pattern is related closely to the development of lung damage (Clark et al, 1998). The rise in CO levels in exhaled air 5 min after smoking a cigarette is a reliable index of smoke inhalation, and Clark et al found that this increase was significantly higher in smokers with emphysema than in those without.…”
Section: Discussionmentioning
confidence: 98%
“…Other authors have found that a distinct tobacco inhalation pattern is related closely to the development of lung damage (Clark et al, 1998). The rise in CO levels in exhaled air 5 min after smoking a cigarette is a reliable index of smoke inhalation, and Clark et al found that this increase was significantly higher in smokers with emphysema than in those without.…”
Section: Discussionmentioning
confidence: 98%
“…Two population based studies have demonstrated that about 30-70% of smokers with COPD are still smokers [3,4]. Some studies have found that smokers with COPD have some specific smoking characteristics, see table 1 [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Der hohe Abhängigkeitsgrad spiegelt sich auch im Inhalationsmuster von Rauchern mit COPD wider: Raucher mit nachgewiesener Obstruktion inhalieren tiefer und schneller als Raucher ohne spirometrische Auffälligkeiten [161,162]. Die beim Lungenemphysem zugrundeliegende Überblähung begünstigt die Ablagerung von Partikeln im Bronchialbaum sowie die Aufnahme von Kohlenmonoxid [163].…”
Section: Tabakrauchen Bei Patienten Mit Copdunclassified